1974
DOI: 10.2307/1940369
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Tolerance in Typha Latifolia without the Evolution of Tolerant Races

Abstract: Clones of the broad—leaved cattail (Typha latifolia L.) and soil samples were obtained from near a zinc smelter and from a control location. In the smelter location, soil zinc concentration was 385 times higher, cadmium content 37 times higher, and lead content 16 times higher. No evidence for the evolution of heavy metal tolerance could be detected in 2 x 2 experiments in which genotypes from both locations were grown on both soils. Growth of genotypes from both locations was inhibited on the heavy metal soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 13 publications
2
41
1
1
Order By: Relevance
“…Such constitutive tolerance has previously been found in a few other species. In Typha latifolia, plants collected from a Zn smelter site did not exhibit higher tolerance than control plants from uncontaminated sites (McNaughton et al, 1974 ;Taylor & Crowder, 1984). Similarly, Thlaspi caerulescens, subsp.…”
Section: Constitutive Metal Tolerance In Arabidopsis Hallerimentioning
confidence: 82%
“…Such constitutive tolerance has previously been found in a few other species. In Typha latifolia, plants collected from a Zn smelter site did not exhibit higher tolerance than control plants from uncontaminated sites (McNaughton et al, 1974 ;Taylor & Crowder, 1984). Similarly, Thlaspi caerulescens, subsp.…”
Section: Constitutive Metal Tolerance In Arabidopsis Hallerimentioning
confidence: 82%
“…Antonovics, Bradshaw & Turner (1971) indicated that there is no clear evidence that a species has constitutional tolerance to heavy metals: evolution has invariably occurred when contaminated habitats are colonized. However, T. latifolia has been reported to show some constitutional tolerance to metals throughout its range (McNaughton et al, 1974;Taylor & Crowder, 1984). Metal tolerance in populations of T. latifolia from metal-contaminated and uncontaminated sites were compared (Zn: McNaughton et al, 1974;Cu and Ni: Taylor & Crowder, 1984) using clonal material generated from rhizome fragments.…”
Section: Introductionmentioning
confidence: 99%
“…However, T. latifolia has been reported to show some constitutional tolerance to metals throughout its range (McNaughton et al, 1974;Taylor & Crowder, 1984). Metal tolerance in populations of T. latifolia from metal-contaminated and uncontaminated sites were compared (Zn: McNaughton et al, 1974;Cu and Ni: Taylor & Crowder, 1984) using clonal material generated from rhizome fragments. Populations from metal-contaminated sites did not show higher metal tolerance than populations from control sites.…”
Section: Introductionmentioning
confidence: 99%
“…Bradshaw, 1965;McNaughton et al, 1974). This paper explores an additional hypothesis which suggests that a high degree of morphological plasticity is an integral part of the mechanism of resource acquisition in productive environments.…”
Section: Introductionmentioning
confidence: 99%